2006
DOI: 10.1897/05-505r.1
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of p-nitrophenol on two Chinese soils as affected by copper

Abstract: Abstract-Heavy metals and organic contaminants often coexist in soils. However, very little information is available regarding the effect of metals on the sorption of organic contaminants onto soils and/or of organic contaminants on metal sorption. In the present study, the effect of Cu on the sorption of p-nitrophenol on two Chinese soils was investigated using a batch-equilibration method for three conditions: Copper and p-nitrophenol were sorbed simultaneously, either Cu or p-nitrophenol was sorbed previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…SOM is the most important component for the adsorption of carbendazim and Cd. Pei et al (2006) discovered that Cu formed inner-sphere complexes with carboxyl and hydroxyl functional groups of soil particles, which also react with p-nitrophenol through H-bond formation, using the X-ray adsorption spectroscopy coupled with the Fourier transform infrared spectroscopy. Similar inner-sphere complexes of Cd might be generated and the ΔH Θ values of carbendazim adsorption also suggested that H-bond was the main interaction.…”
Section: Adsorption and Desorption Of Carbendazim And CD Under Combinmentioning
confidence: 99%
“…SOM is the most important component for the adsorption of carbendazim and Cd. Pei et al (2006) discovered that Cu formed inner-sphere complexes with carboxyl and hydroxyl functional groups of soil particles, which also react with p-nitrophenol through H-bond formation, using the X-ray adsorption spectroscopy coupled with the Fourier transform infrared spectroscopy. Similar inner-sphere complexes of Cd might be generated and the ΔH Θ values of carbendazim adsorption also suggested that H-bond was the main interaction.…”
Section: Adsorption and Desorption Of Carbendazim And CD Under Combinmentioning
confidence: 99%
“…Electron beam energy was 2.2 GeV with a storage ring beam current of 80 mA. Sample preparation and data collection followed the methods described in our w a t e r r e s e a r c h 4 3 ( 2 0 0 9 ) 2 4 0 9 -2 4 1 8 previous research (Pei et al, 2006). Briefly, data analysis was performed with WinXAS2.1 following background correction and normalization, Cubic spline, Fourier transformation and reverse Fourier transformation, and EXAFS fitting.…”
Section: Xas Measurements and Data Analysismentioning
confidence: 99%
“…However, contaminants often exist in mixtures in the environment, where they may affect each other's sorption. Heavy metals and organic contaminants coexist at many contaminated sites (Dai et al, 2007;Sprovieri et al, 2007), and coexisting heavy metal ions affect the adsorption of organic contaminants to soil, peat and charcoal (Pei et al, 2006(Pei et al, , 2007Chen et al, 2007). A few studies have been reported on competitive sorption between metals (Li et al, 2003b) or between organic contaminants on CNTs (Yang et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports available in this field [29,30]. In the present study, Pb and phenol were chosen as representatives of heavy metals and toxic organic pollutants, respectively.…”
Section: Introductionmentioning
confidence: 99%